Covid-19, Classical Subjects and the Classroom: Teachers' Feedback from Summer 2020. Issue 42 (2020) - Dixon, Jessica
Abstract: The Classical Association Teaching Board (CATB) surveyed Classics teachers in the United Kingdom from 20th August to 9th September 2020 to gauge views about the impact on teaching of the national lockdown during the covid-19 pandemic. 164 teachers from both the state and independent sectors completed the survey. There were three areas of focus in the survey. First, the impact on pupils of the grade awarding process after the cancellation of GCSE and A Level examinations in 2020. Second, how confident teachers were in preparing for the 2021 examinations after the loss of five months of face-to-face teaching. Third, reactions to Ofqual's consultation process on changes to the format of the 2021 examinations. This article brings together the responses to the survey and details how the unprecedented closure of schools affected the teaching of Classics. It will also explain how the CATB continues to support Classics teachers and the teaching of classical subjects in UK schools.